IN-VITRO CYTOTOXICITY OF INDIAN BEE PROPOLIS ON CANCER CELL LINES - R SHUBHARANI; V SIVARAM; B R KISHORE (International Journal of Pharma and Bio Sciences, 2014)
Propolis is a natural resinous hive product collected by honeybees from exudates of plant sources. It has been used in folk medicine due to its various chemical compounds with biological properties since ancient times. The aim of this study was to compare the chemical constituents and to evaluate the in-vitro cytotoxicity and hemolytic activity of Indian propolis against human breast cancer (MCF 7), colon cancer (HCT 116), and prostate cancer (PC 3) cell lines by MTT assay. The propolis extracts were incubated with cancer cell lines for 24 hours, cytotoxicity was measured colorimetrically and the IC50 value was calculated. Propolis samples were analyzed by GC-MS and 44 compounds were identified. The results indicated that inspite of the differences in the chemical composition of propolis collected from different geographic locations all the samples exhibited significant cytotoxic activity and did not affect normal cells. It is concluded that the Indian propolis is a potential natural source of chemopreventive agent.